2024
DOI: 10.1111/nph.19557
|View full text |Cite
|
Sign up to set email alerts
|

Auxin co‐receptor IAA17/AXR3 controls cell elongation in Arabidopsis thaliana root solely by modulation of nuclear auxin pathway

Monika Kubalová,
Karel Müller,
Petre Ivanov Dobrev
et al.

Abstract: Summary The nuclear TIR1/AFB‐Aux/IAA auxin pathway plays a crucial role in regulating plant growth and development. Specifically, the IAA17/AXR3 protein participates in Arabidopsis thaliana root development, response to auxin and gravitropism. However, the mechanism by which AXR3 regulates cell elongation is not fully understood. We combined genetical and cell biological tools with transcriptomics and determination of auxin levels and employed live cell imaging and image analysis to address how the auxin respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…IAA is synthesized in plants and specifically binds to the auxin receptor SCF TIR1 in the nucleus, thus starting the auxin signal transduction pathway. Recently, a study showed that TIR1/AFB-Aux/IAA pathway rapidly modulates root cell elongation [ 36 ]. In our experiment, only the AUX/IAA-encoding genes are differentially expressed, as they are more sensitive to changes in IAA content.…”
Section: Discussionmentioning
confidence: 99%
“…IAA is synthesized in plants and specifically binds to the auxin receptor SCF TIR1 in the nucleus, thus starting the auxin signal transduction pathway. Recently, a study showed that TIR1/AFB-Aux/IAA pathway rapidly modulates root cell elongation [ 36 ]. In our experiment, only the AUX/IAA-encoding genes are differentially expressed, as they are more sensitive to changes in IAA content.…”
Section: Discussionmentioning
confidence: 99%